Validity of Account-Blocking Clauses in Standard Agreements Between Crypto-Asset Platforms and Consumers in Indonesia - Winata, Christopher Andrew; Kurnia, Ida (Jurnal Ilmu Hukum Kyadiren, 2026)
The rapid growth of crypto-asset transactions in Indonesia has led to an increased reliance on electronic agreements containing standard clauses unilaterally drafted by digital platforms. However, the unilateral authority to block user accounts raises concerns regarding legal validity and potential violations of consumer rights. This study examines the legal framework governing standard clauses in electronic agreements on crypto-asset platforms and assesses the validity of account-blocking clauses under the Consumer Protection Law (UUPK) and the Indonesian Civil Code (KUH Perdata). Using a normative juridical method, the research analyzes statutory regulations, court decisions, and relevant literature. The findings indicate that although the standard clause satisfies the elements of a valid agreement under Article 1320 of the Civil Code, a unilateral account-blocking clause violates Article 18 of the UUPK because it grants disproportionate authority to business actors and may undermine consumer rights without a legitimate legal basis. The study concludes that account blocking is legally valid only when conducted pursuant to an order issued by a competent authority and in accordance with consumer protection principles.